To wake-up, or not to wake-up: that is the Hamletic neurocritical care question! - Prisco, L; Citerio, G (BioMed Central, 2012)
The need for a reliable neurological evaluation in severely brain-injured patients conflicts with sedation, which is routinely administered. Helbok and colleagues prospectively evaluated in a small cohort of 20 sedated severely brain-injured patients the effects of a wakeup test on intracranial pressure (ICP), brain tissue oxygen tension and brain metabolism. The test has been considered potentially risky on 34% of the study days. When the test is performed, ICP and cerebral perfusion pressure increase, usually slightly, except in a subgroup of patients with lower cerebral compliance where marked ICP and cerebral perfusion pressure changes were recorded. In this cohort, the information gained with the wake-up test has been negligible. Given the current little knowledge about the benefits of interruption of continuous sedation in brain-injured patients, it is extremely important to adopt multiple monitoring modalities in neurocritical care in order to escape wake-up tests in those patients who will potentially be harmed by this procedure. Once the clinical condition will improve, sedation needs to be tapered and suspended as soon as possible.